(untitled) (Bangladesh Journal of Botany, 2025)
Cocoa is an important cash crop grown in southern parts of India. Though many cocoa varieties have been released for cultivation, there is no variety recommended for cultivation exclusively for Tamil Nadu. Therefore, the present investigation was undertaken to study the performance of nine identified cocoa clones for its growth, pod yield and yield attributing traits for subsequent research programmes. Mean average pod yield among the clones varied from 9.40 to 15.3/tree-/year. Clone TNAU CC 5 significantly higher pod yield (15.31), number of fresh beans/pod (37.55), pod weight (382.93 g). Pod set percentage in the juvenile stage varied from 2.1 (TNAU CC 9) to 3.3(TNAU CC 5). Dried beans are the prime economic product of cocoa, and single dry bean weight ranged from 0.80 to 0.92 g. In the present study, the mean value for theobromine and caffeine, catechin and epicatechin content was 7.35 and 1.76 mg/g, 0.91 and 2.19 mg/g, respectively. Considering the most economic traits of cocoa, TNAU CC 5 appears to be the most suitable clone for commercial cultivation in the region. Bangladesh J. Bot. 54(1): 137-144, 2025 (March)